2018
DOI: 10.1097/qai.0000000000001567
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of HIV, HIV Risk Perception, and HIV Worry Among Adolescent Girls and Young Women in Lilongwe, Malawi

Abstract: Most AGYW perceive little risk of HIV acquisition, even those at highest risk. As a critical gap in the HIV prevention cascade, accurate risk perception is needed to tailor effective and sustained combination prevention strategies for this vulnerable population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
78
3
18

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(107 citation statements)
references
References 46 publications
8
78
3
18
Order By: Relevance
“…Among the general population in Nigeria, the HIV stigma level has declined [13], however this is yet to be determined among young adolescents aged 10-14. Similarly on risk perceptions, some studies in Africa [14][15][16] have found perceived low and inaccurate reporting of HIV risks among adolescents. It is therefore beneficial to accurately understand why young adolescents perceive themselves to be at low risk in order to address misconceptions associated with their beliefs.…”
Section: Introductionmentioning
confidence: 99%
“…Among the general population in Nigeria, the HIV stigma level has declined [13], however this is yet to be determined among young adolescents aged 10-14. Similarly on risk perceptions, some studies in Africa [14][15][16] have found perceived low and inaccurate reporting of HIV risks among adolescents. It is therefore beneficial to accurately understand why young adolescents perceive themselves to be at low risk in order to address misconceptions associated with their beliefs.…”
Section: Introductionmentioning
confidence: 99%
“…at a more advanced stage of the disease, interfering with its prognosis and progression of comorbidities. (19) The study found a higher prevalence of high clinical risk among cases with detectable viral load, LT-CD4+ between 200-500 cells/mm 3 , two or more opportunistic diseases at diagnosis, two or more clinical manifestations or a chronic disease.…”
Section: Discussionmentioning
confidence: 74%
“…Even if increasing risk perception leads to increased condom use, low levels of risk perception in the population would mean that only limited numbers of people would increase condom use after increasing risk perception, so effects on population-level HIV incidence would be limited. Risk perception has often been found to be low even among those engaging in behaviours associated with increased risk of HIV infection (33)(34)(35), which may indicate that the change in prevention behaviour attributable to changes in risk perception is limited. However, again, lack of longitudinal studies limits our understanding of the degree to which behaviour can be attributed to change in risk perception.…”
Section: Introductionmentioning
confidence: 99%